Perencanaan Strategi Sistem Informasi Pada Vion Coffee Menggunakan Metode Anita Cassidy - Winata Suryana; Apriade Voutama (LKP KARYA PRIMA KURSUS, 2026)
The development of information systems and technology requires businesses in the food and beverage sector, including coffee shops and restaurants, to align their information systems with their business goals. Vion Coffee currently uses Opaper (POS) and Absensiku application. However, these systems are not yet integrated, so they have not yet fully supported operational activities and decision-making processes. Therefore, a strategic information system planning is needed to improve operational effectiveness and business competitiveness. This research uses the Anita Cassidy method, comprising four stages: visioning, analysis, direction, and recommendation. Data were collected through interviews and analyzed using several tools, such as the Value Chain, Porter’s Five Forces, SWOT analysis, and the McFarlan Grid. Based on the analysis result, four IS/IT solution recommendations were proposed. These solutions are arranged on a multi-year development roadmap, considering business needs, cost estimates, and implementation schedules. This strategic plan is expected to guide the gradual, sustainable development of information systems at Vion Coffee to improve operational performance and support future business growth.